Suitability of intercropping flue-cured tobacco (Nicotiana tabacum) with lentil (Lens culinaris) - ISLAM, M N; MIAN, M A K; PAUL, R K; ALI, M O (The Indian Journal of Agricultural Sciences, 2013)
In a 2-year Geld experiment, tobacco (Nicotiana tabacum L.)  was intercropped with lentil (Lens culinaris Medikus).Signitlcantly highest yields of cured tobacco ieaf (1 970 kg/ha) and lentil (980 kg/ha) were obtained from the pure stand.Among intercropping treatments. tobacco paired row + 50%  lentil gave the highest land-equivalent ratio (1.49), tobacco equivalent yield (2 109 kg/ha), net return (Rs 52 864/ha), monetary advantage (Rs 20 804/ha) and benfit : cost ratio        (6: 08).